Poverty, income inequality and living standards in Ireland: Fourth annual report - Roantree, Barra; Bertrand, Maître; Russell, Helen (ESRI, 2024)
This report is the fourth from an ESRI research programme funded by Community Foundation Ireland, which seeks to address gaps in our knowledge and understanding of poverty, income inequality and living standards in Ireland. The thematic chapter in this year’s report considers life satisfaction, civic and social participation. The key findings of this year’s report are as follows: Income growth and inequality After a decade of uninterrupted growth, the latest data from the Survey of Incomes and Living Conditions (SILC) show inflation has left average real disposable income lower than it was two years earlier. After tax and transfer incomes adjusted (equivalised) for household size have fallen in real terms at both the mean and median: by 2.2 per cent and 5.4 per cent respectively between 2021 and 2022. This was sufficient to leave average incomes lower than they were in 2020, with the decline largely a result of the rise in prices that has followed the COVID-19 pandemic and the invasion of Ukraine. A notable exception to this decline in average incomes is for those aged 65+. Although average equivalised disposable incomes declined in real terms by around 3 per cent for those under 65 on both a Before Housing Costs (BHC) and After Housing Costs (AHC) basis, they grew by 3 per cent for those aged 65+. Strikingly, equivalised AHC income is now on average higher for those above age 65 than those under 65. This growth has been driven by a rise in income from employment, self-employment and the rental of property or land, as well as a rise in the share of those aged 65+ with a spouse in paid work. Incomes have stagnated across the rest of the distribution, halting the sustained decline in measures of income inequality that has been seen since 2017. Between 2012 and 2021, incomes grew fastest at the bottom of the income distribution, leading to a decline in measures of income inequality including the Gini coefficient which summarises the level of income inequality as a number between 0 (where everyone has the same income) and 1 (where one person has all income). While we estimate the Gini coefficient fell from 0.296 in 2012 to 0.261 in 2021, this decline appears to have stalled with real incomes stagnating across the distribution over the last two years of data. Income poverty and material deprivation Rates of material deprivation have risen across the population as a whole for the second year in a row. The share of individuals unable to afford two or more items from a list of ten essentials has increased from 13.2 in 2021 to 16.3 per cent in 2023, with over half of those renting from an approved housing body, local authority or receiving Housing Assistance Payment (HAP) reporting being unable to do so. Rates of material deprivation have also increased for children, with a fifth of those aged 0–17 experiencing material deprivation compared to one in ten for those aged 65+. Despite falling for those aged 65+, measures of income poverty have risen for children when accounting for housing costs. Rates of income poverty are particularly high in households where the youngest child is aged 0–5, with a quarter of those in such households (amounting to almost 250,000 children and parents) below the AHC income poverty line. This suggests additional measures – such as a second tier of child benefit targeted at low-income families, explored by Roantree and Doorley (2023) in last year’s report – may need to be considered if Government commitments to reduce rates of child poverty are to be achieved. Overall, these trends pose a real challenge for the Government in the upcoming Budget. While inflation is falling and those in employment are likely to see a rise in their real incomes, temporary cost-of-living-related payments have played a key role in maintaining the income of those at the bottom of the distribution. Given the limited resources allocated to tax and welfare measures in the recent Summer Economic Statement (Department of Finance, 2024), it is unlikely increases to core payments will be sufficient to offset the withdrawal of temporary payments, meaning that the incomes of those at the bottom of the distribution are likely to lag behind those of the rest of the population with consequences for income poverty, inequality and material deprivation. Life Satisfaction, Civic Participation and Social Contact Levels of life satisfaction are strongly associated with income poverty and even more so with material deprivation. Being deprived reduces life satisfaction by over one point on a ten-point scale. This effect is larger than that observed for poor health and the pandemic. Life satisfaction declined significantly during the pandemic period (2020 and 2021). Particularly sharp declines were seen among young people and lone parents. The relationship between poverty and life satisfaction is similar for most groups; however, we find that deprivation has a stronger effect on satisfaction for those aged 35–55 and 55–64 years compared to the older age group. This is likely to reflect greater financial responsibilities. There is also a somewhat stronger association between income poverty and life satisfaction for men. Income poverty and deprivation also have a depressing effect on civic participation (formal and informal volunteering and political participation). Pre-pandemic in 2015, 61 per cent of the deprived did not participate in any of these activities in the previous 12 months compared to 49% of the non-deprived. The pandemic was associated with a sharp decline in civic participation across all groups. The average score on civic participation dropped by half, falling from 0.79 in 2015 to 0.44 in 2022. Additionally, although the gap between those in income poverty and deprived and others narrowed only slightly, their civic participation remained significantly lower by roughly one quarter. Civic participation is lower among the youngest and oldest age groups, migrants from the EU and outside the EU. However, the relationship between income poverty/deprivation and civic participation is somewhat weaker for the non-EU cohort than for those born in Ireland. This may reflect greater involvement in religion-based volunteering but the data do not allow us to disaggregate this effect further. Social participation measured through frequency of face-to-face or other contact with family and friends, is also significantly lower among those who are deprived or who are income-poor compared to other groups. Social participation declined between 2015 and 2022 across all groups, again reflecting the impact of the pandemic. Income poverty is not associated with the frequency of social contact once other factors are taken into account. However, those who are deprived have significantly fewer contacts. The reduction in social contact associated with deprivation (-0.9 on a ten-point scale) is greater than that associated with poor health (-0.8) and with the pandemic (-0.5). The relationship between deprivation and social contact is the same for all the sub-groups examined, except that it has a somewhat weaker effect for the youngest age group. This may arise because digital/remote contact is maintained despite deprivation.